ROOT COVERAGE USING THE SUBEPITHELIAL CONNECTIVE TISSUE GRAFT OR THE ACELLULAR DERMAL MATRIX FOR THE TREATMENT OF GINGIVAL RECESSION: A CLINICAL STUDY - Sumana, Shula Zuleika; Masulili, Sri Lelyati C; Lessang, Robert (International Journal of Applied Pharmaceutics, 2018)
Objective: This study aims to evaluate periodontal clinical conditions after treatment for gingival recession (GR) using subepithelial connective tissue graft (SCTG) and acellular dermal matrix (ADM). Methods: Ten patients with Miller's ClassÂ I and II recessions that had been treated with SCTG or ADM at the Periodontics Outpatient Department at Universitas Indonesia were selected for this study. The pre-operative data for GR, clinical attachment levels (CAL), and attached gingiva (AG) were retrieved from the patients' medical records. The patients were recalled and the post-operative data were recorded. Results: The application of SCTG and ADM yields significant changes to GR, CAL, and AG levels. AÂ comparison of two groups at the post-operative assessment stage showed no statistically significant differences, in terms of GR, CAL, and AG. Conclusion: SCTG and ADM yield similar outcomes in the treatment of GR. As such, ADM may be suggested as an alternative to SCTG for root coverage.